Non-applicability of evidentiary conventions in Judicial District of Huánuco - Ventocilla Ricaldi, Edwin Francisco (2022)
The non-applicability of the evidentiary conventions in the preliminary investigation courts of the Judicial District of Huánuco, in the period 2018-2022, is due to the fact that the procedural parties did not propose them in the intermediate stage. Proof of this is that the judges did not approve them or disassociate themselves. It is also due to the fact that judges do not have legal protection to propose or formulate evidentiary conventions in court hearings, since this does not contribute to the principles of economy, speed and procedural efficiency, as long as they send uncontroversial proven facts for debate, which become one more tributary of overload for the oral trial.